Northrop Frye and the phenomenology of myth - Gill, Glen Robert, 1969- (Frye studies., 2006)
With excursions into fields such as literary theory, depth psychology, theology, and anthropology, Northrop Frye and the Phenomenology of Myth is essential to the understanding of Frye's important mythological work.